The impact of agricultural investments on state capacity: A comparative analysis of Ethiopia and Ghana. (June 2016) - Lavers, Tom; Boamah, Festus
Highlights: The links between agricultural investments and state capacity are under-researched. Agricultural investments can provoke the re-configuration of state–society relations. These processes transform the state itself. Investments in Ethiopia build state capacity whereas the reverse is the case in Ghana. A systematic comparative analysis of impacts of investments offers potential for mid-level theorising. Abstract: The first wave of research on the 'global land grab' largely focused on the international drivers of investment and impacts of individual projects in host countries. More recent studies have acknowledged the important roles played by both host states and societal organisations in these deals. However, there has been little attempt to analyse how processes of agricultural investments also transform the state itself. The present paper builds on theories regarding the social roots of state power and the literature on the links between land and authority, to construct a framework that can be used to explore these linkages. The central argument of the paper is that in situations of overlapping authority between state and societal organisations—which is common in Africa—increased agricultural investment requires infrastructure development and can provoke changes in power relations between state and society that have important implications for state capacity. We illustrate this by examining the recent investment trends in two countries that have figured prominently in the 'land grab' literature but where land tenure regimes and state–society relations take markedly different forms—Ethiopia, where a 'strong' state has actively promoted agricultural investments as part of a developmental and state-building project that has enhanced its territorial control; and Ghana where chiefs have taken advantage of increased demand from investors in an attempt to (re-)assert their authority over land vis-à-vis the state and other societal organisations.